Investigations of pulsed plasma streams generated by “Prosvet” device operated with different gases - Byrka, O.V.; Bandura, A.N.; Chebotarev, V.V.; Garkusha, I.E.; Ladygina, M.S.; Marchenko, A.K.; Trubchaninov, S.A.; Tsarenko, A.V.; Shevchuk, P.B.; Tereshin, V.I. (Вопросы атомной науки и техники, 2006)
The paper presents the investigations of plasma streams generated by pulsed plasma gun “Prosvet” operated with
different gases: krypton (m = 84), nitrogen (m = 14) and helium (m = 4). Contour parameters of working gas spectral
lines (full intensities and half-widths) are used for determination of spatial distributions of the electron density and
temperature. Temporal distributions of the spectral lines intensities (both neutrals and ions of working gas), impurity
spectral lines and continuum intensities are analyzed. Plasma stream velocity was estimated by time-of-flight method
between two monochromators (MUM) connected with photo-multiplier. Longitudinal distributions of the plasma
pressure for different time moments and varied distances from the accelerator output have been used for investigation of
the plasma stream dynamics and study the plasma compression in the focus region for different operational regimes of
plasma accelerator. Experiments show that operation regime of the accelerator and plasma stream parameters strongly
depend on the gas atomic mass.